Evaluation of qPCR on blood and skin microbiopsies, peripheral blood buffy coat smear, and urine antigen ELISA for diagnosis and test of cure for visceral leishmaniasis in HIV-coinfected patients in India: a prospective cohort study. Issue 4 (30th April 2021) - Owen, Sophie I; Burza, Sakib; Kumar, Shiril; Verma, Neena; Mahajan, Raman; Harshana, Amit; Pandey, Krishna; Cloots, Kristien; Adams, Emily; Das, Pradeep
Abstract : Introduction: HIV coinfection presents a challenge for diagnosis of visceral leishmaniasis (VL). Invasive splenic or bone marrow aspiration with microscopic visualisation of Leishmania parasites remains the gold standard for diagnosis of VL in HIV-coinfected patients. Furthermore, a test of cure by splenic or bone marrow aspiration is required as patients with VL-HIV infection are at a high risk of treatment failure. However, there remain financial, implementation and safety costs to these invasive techniques which severely limit their use under field conditions. Methods and analysis: We aim to evaluate blood and skin qPCR, peripheral blood buffy coat smear microscopy and urine antigen ELISA as non-invasive or minimally invasive alternatives for diagnosis and post-treatment test of cure for VL in HIV-coinfected patients in India, using a sample of 91 patients with parasitologically confirmed symptomatic VL-HIV infection. Ethics and dissemination: Ethical approval for this study has been granted by The Liverpool School of Tropical Medicine, The Institute of Tropical Medicine in Antwerp, the University of Antwerp and the Rajendra Memorial Research Institute of Medical Science in Patna. Any future publications will be published in open access journals. Trial registration number: CTRI/2019/03/017908.